Sudden cardiac death in epilepsy disappoints, but epileptologists keep faith - Scorza, Fulvio A.; Cavalheiro, Esper A.; Costa, Jaderson Costa da (Arquivos de Neuro-Psiquiatria, 2016)
Sudden unexpected death in epilepsy (SUDEP) is the most common cause of death in people with intractable epilepsy. Probably, optimization of seizure control will prevent some of these deaths. Briefly, we integrated in this paper some data about the epidemiology, risk factors, etiology, and preventative measures in the management of SUDEP.
Keywords: epilepsy; death, sudden